Effects of cultured human adipose‐derived stem cells transplantation on rabbit cornea regeneration after alkaline chemical burn. Issue 1 (2nd November 2012) - Lin, Hsiu‐Fen; Lai, Yung‐Chang; Tai, Chih‐Feng; Tsai, Jin‐Lian; Hsu, Huan‐Chen; Hsu, Ruey‐Fen; Lu, Sheng‐Nan; Feng, Nan‐Hsiung; Chai, Chee‐Yin; Lee, Chung‐Hsun
Abstract: Ocular chemical burn is a severe injury with poor outcomes. Immediate and appropriate management is highly related to prognosis. We studied the effect of cultured human adipose tissue‐derived stem cells on the regeneration of the rabbit cornea after alkaline chemical burn, using used human adipose tissue‐derived stem cells as the source material. Immediately after the chemical burn, the experimental eye received a single subconjunctival injection of a stem cell suspension (1.3 × 10 5 cells/0.2 mL), with the other eye serving as control. Rabbits were sacrificed and specimens taken 30 days after injection. The experimental group showed faster wound healing than the control group, and the result for the experimental group was clearer cornea medium. Histologically, there were five to six epithelial cell layers on the corneas of the experimental group as compared to two to three cell layers on the corneas of the control group. Wilcoxon signed rank test showed a significant difference in the epithelial cell layers between the two groups. Surface markers for connexin 43 (Cx43), β‐catenin, E‐cadherin, and P63 were analyzed. Cx43 and β‐catenin showed significant change, as determined by the Wilcoxon signed rank test, which indicated good cell renewal during repair of the corneal epithelium damaged by the chemical burn. E‐cadherin and P63 showed no significant change during the epithelium healing process. Transplantation of cultured human adipose tissue‐derived stem cells as a treatment for a corneal chemical burn promotes cell renewal and assists in damage repair.